Environmental impact study of the sightseeing electric vehicle supply chain based on the B2C e-commerce model and LCA framework - Wei Xia; Chunjun Luo; Li Cai; Juan Yan; Xiaojiang Zhou; Yuan Zhang (Energy Informatics)
Abstract Studying the impact of the electric vehicle supply chain on the environment is crucial for determining the future development direction of the industry. We have developed a method for evaluating the impact of supply chains on the environment based on a lifecycle framework. This method innovatively seeks the connection between the lifecycle process of physical products and the supply chain, and organizes the environmental impact assessment factors of the electric vehicle supply chain from three aspects: physical resources, power energy, and waste emissions, in order to construct an LCA fuzzy comprehensive evaluation model for the electric vehicle supply chain. For the first time, the research method of transforming qualitative analysis into quantitative data was introduced into the life cycle environmental impact assessment, and empirical research was conducted using the supply chain of sightseeing electric vehicles as an example. The results indicate that the scrapping stage of electric vehicles has the most severe impact on the environment. Strengthening research on strategies or technologies for handling waste batteries and automobiles is key to improving the environmental performance of the supply chain. This method breaks through the requirements and limitations of traditional life cycle assessment methods on data sources and parameters, avoids large-scale calculations that cannot be separated from subjective factors in traditional methods, simplifies the process of supply chain environmental impact assessment, shortens the evaluation time, and improves the efficiency of environmental impact assessment. It is more practical and has good application prospects.